Determination of the Effect of Bekinox Fibers on the Fabrics Specific Surface Electrical Resistance - Dzmitry Ryklin; Dzmitry Kvetkovsky (Vestnik of Vitebsk State Technological University, 2021)
The object of research is antistatic fabrics containing Bekinox steel fibers. The aim of the work is to determine the minimum percentage of Bekinox fibers in a fabric which provides a required level of antistatic properties. The information received will be used for development of the method to design fabrics for special application. As a result of statistical processing of experimental data a mathematical model was developed that describes the dependence of the surface electrical resistance of fabric on the Bekinox steel fibers percentage in their structure in the range from 0 to 1 %. It was found that the deviation of the observed value of the electrical resistance of fabrics from the predicted one does not exceed 1 degree of order regardless of the location of antistatic yarns in their structure. Based on the analysis of the resulting model and the requirements for antistatic fabrics recommendations for their design have been developed. Объект исследований – антистатические ткани, содержащие в своем составе стальные волокна Bekinox. Цель работы – определение минимального количества волокон Bekinox в ткани, обеспечивающего заданный уровень антистатических свойств, для последующего учета по- лученной информации при разработке методики проектирования тканей специального назначения. В результате статистической обработки экспериментальных данных построена математическая модель, описывающая зависимость удельного поверхностного электрического со- противления тканей от процентного содержания в их структуре стальных волокон Bekinox в диапазоне от 0 до 1 %. Установлено, что отклонение фактического значения удельного электрического сопротивления тканей от рас- четного не превышает 1 порядка независимо от расположения в их структуре антистатических нитей. На основании анализа полученной модели и требований, предъявляемых к антистатическим тканям, разработаны рекомендации по их проектированию.